Studi Kritis Terhadap Penetapan Sertifikasi Produk Halal Oleh Majelis Ulama Indonesia Sulawesi Selatan Perspektif Maslahah - Teguh Dermawan; Ahmad Musyahid; Abdul Syatar (widya balina, 2025)
This study critically examines the halal product certification process conducted by the Indonesian Council of Ulama (Majelis Ulama Indonesia, MUI) of South Sulawesi from the perspective of maslahah (public interest). The research is grounded in the urgent need to protect Muslim consumers, particularly in light of the growing consumption of both local and imported products that often lack clear halal status. While numerous studies have explored halal certification at the national level, there remains a significant gap in examining the regional dynamics and implementation of MUI fatwas, especially in South Sulawesi. This study aims to analyze the approaches employed by MUI South Sulawesi in determining halal certification and assess the extent to which maslahah serves as the guiding principle in their process. The research adopts a field research methodology with a descriptive qualitative approach and uses ushuliyyah (Islamic legal methodology) as its analytical framework. Data collection was carried out through observation, interviews, and documentation. The findings reveal that MUI South Sulawesi consistently upholds the principles of Islamic law in the halal certification process, emphasizing critical ingredients, production processes, and the cleanliness of facilities. Although the use of additives such as coloring and preservatives is permitted, it is contingent upon their halal status and freedom from impurities (najis). This approach reflects a moderate application of maqāṣid al-sharī‘ah, demonstrating adaptability to industrial developments while maintaining a cautious and principled stance. The study underscores the importance of transparency and education for business actors, and recommends further research focusing on post-certification supervision or comparative studies across regions. These findings offer valuable contributions to strengthening Indonesia’s halal assurance system based on the principles of public welfare.